Addressing the evidence to practice gap for complex interventions in primary care: a systematic review of reviews protocol. Issue 6 (23rd June 2014) - Lau, Rosa; Stevenson, Fiona; Ong, Bie Nio; Dziedzic, Krysia; Eldridge, Sandra; Everitt, Hazel; Kennedy, Anne; Kontopantelis, Evangelos; Little, Paul; Qureshi, Nadeem; Rogers, Anne; Treweek, Shaun; et al.
Abstract : Introduction: Getting the results of research implemented into routine healthcare is often a challenge. The disconnect between the development and implementation of evidence into practice is called the 'second translational gap' and is particularly apparent in primary care. To address this gap, we plan to identify, summarise and synthesise currently available evidence by undertaking a systematic review of reviews to: (1) explore barriers and facilitators of implementation of research evidence or complex interventions, and (2) assess the effectiveness of strategies in facilitating implementation of complex interventions in primary care. Methods and analysis: This is a protocol for a systematic review of reviews. We will search MEDLINE, EMBASE, the Cochrane Library, CINAHL and PsycINFO up until December 2013. We will check reference lists of included studies for further studies. Two authors will independently screen the titles and abstracts identified from the search; any discrepancies will be resolved by discussion and consensus. Full-text papers will be obtained and relevant reviews will be selected against inclusion criteria. Eligible reviews have to be based on predominantly primary care in developed countries and examine either factors to implementation or, the effectiveness of strategies to optimise implementation. Data from eligible reviews will be extracted using standardised data abstraction forms. For barriers and facilitators, data will be synthesised using an interpretative meta-synthesis approach. For implementation strategies, findings will be summarised and described narratively and synthesised using a framework approach. All findings will be reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Ethics and dissemination: Ethical approval is not required. The review findings will inform the work of the design and implementation of future studies and will be of interest to a wide audience including health professionals, researchers, health service or commissioning managers and policymakers. Trial registration number: Protocol registration number (PROSPERO CRD42014009410).